Case report: Cerebellar swelling and hydrocephalus in familial hemophagocytic lymphohistiocytosis - Yoshida, Taro; Moriya, Kunihiko; Oikawa, Keisuke; Miura, Shoko; Asakura, Yoshiko; Tanifuji, Sachiko; Kusano, Shuji; Endo, Mikiya; Akasaka, Manami (Frontiers in Pediatrics, 2022)
Familial hemophagocytic lymphohistiocytosis (FHL) is a severe inborn error of immunity caused by a genetic defect in the function of cytotoxic T and NK cells. There are only a few reported cases of FHL with diffuse swelling of the cerebellum and obstructive hydrocephalus. We report a case of FHL3 with neurological symptoms associated with cerebellar swelling and obstructive hydrocephalus. A male patient was hospitalized several times due to fever and decreased feeding, hepatosplenomegaly, and cytopenia since the first month of life. At 7 months of age, he was seen for disturbance of consciousness. Brain magnetic resonance imaging revealed a signal intensity in the bilateral cerebellar hemispheres, diffusely increased periventricular white matter, and ventriculomegaly. Although he was treated with methylprednisolone pulse therapy, he was unresponsive to the treatment. He was then transferred to a local hospital after tracheotomy, but subsequently died. Targeted clinical sequencing revealed a homozygous splice-site mutation in UNC13D. Pediatric hemophagocytic lymphohistiocytosis (HLH) includes some cases of central nervous symptom (CNS)-isolated HLH or CNS HLH preceding systemic lesions, which often do not initially meet the diagnostic criteria for FHL. Patients with FHL initiated by cerebellar symptoms may present with an atypical clinical course for HLH, leading to delayed diagnosis and poor outcome. Despite the usefulness of a combination of a high percentage of lymphocytes in the peripheral leukocytes, low lactate dehydrogenase level, and high sIL2R/ferritin ratio are indicated for identifying FHL, the diagnosis may be missed due to absence of these results. Pre-symptomatic diagnosis of FHL by newborn screening and subsequent early treatment of patients with a predicted poor prognosis may contribute to better outcomes.